Studies in Glycolipids - Demir, Kenan (Cambridge Scholars Publishing, 2021)
The collection of essays reviews and explores current issues concerning glycolipids in their broadest sense. Its overview of glycolipids, gangliosides and ceramides, and their connection with related diseases, the immune system, cancer and infections offers a comprehensive presentation of current trends, data and possible developments in health sciences, pharmacology and industry.